WPSAR after 14 volumes: achievements and future directions - Arashiro, Ashley; McPherson, Michelle; Andaya, Roxanne; Rivada, Don; Olowokure, Babatunde (Western Pacific Surveillance and Response, 2023)
In this editorial, the Editorial Team reviews WPSAR journal’s achievements over its 14 volumes so far, including the assignment of its first impact factor, and announces an expanded journal scope.